Implementation Of Teacher And Lecturer Policy At Vocation Education System Of The Indonesian Navy - Sutristyanto, Isworo; ., Sumartono; S. Haryono, Bambang; Mindarti, Lely I. (International Journal of Scientific Research and Management (IJSRM), 2018)
Nowadays, the policy of national higher education has an influence on  higher education in the Indonesian Navy in patterns and structures, types of education, educational outcomes or graduates of each educational strata. The human resources of the Navy were built by an using expert system with the field of each assignment being scholar soldier, with the development domain is Cognitive, Affective and Psychomotor Domains Granding. The equalization of graduates between academic and vocational education influences on the quantity and quality of standardized military lecturers as educators in the Navy education system which is harmonized with the prevailing national policy. Based on the existing gap due to the implementation of lecturer policy, the efforts that have been done, the purposes of this study are : 1) Describe and analyze the implementation of teacher and lecturer policy on Higher Education Vocation of the Indonesian Navy service vocation; 2) Finds the implementation model of policy of teacher and lecturer in higher education of vocation of the Indonesian Navy. In this research, the paper used Merilee S. Grindle model approach. It model uses to describe the implementation of policy of teachers and lecturers in higher education vocational service of the Indonesian Navy. The result of the policy implementation on vocation system of teacher and lecturer in higher education system of the Indonesian Navy has not given any significant result change, because there are still many obstacles in the process. The model of policy implementation of teacher and lecturer in higher education vocation of the Indonesian Navy officially started by synchronizing policy between the Higher Education Institution and the Indonesian Navy  then it is passed down to specific socialization program to support of lecturer policy objectives.